Village Government Management in Increasing BUMDes Productivity in Balongsari Village, Rawamerta District, Karawang Regency - Widya Indah Pradani; Eka Yulyana; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
Village Owned Enterprises or BUMDes are village-owned enterprises formed with the aim of improving the local village economy. Based on the research result, BUMDes in Balongsari Village only has an entertainment stage business for now. However for future plans, The Balongsari Village Government together with BUMDes want to develop Balongsan Village into a Tourism Village because of the tourism potential it has, namely the Rawagede Monument and Makom Jaka Tingkir and want to bulid partners with opak farmers in Balongsari Village. Not maximize, seen and the type of business that is still small and the lack of socialization to the community has made the BUMDes of Balongsari Village descrease in productivity and couple with the covid-19 pandimic which has made the entertainment stage as a type of business that BUMDes have currently does not work while the research method used in. This research is a qualitative method with this method, the researches obtained the results that the productivity of BUMDes in Balongsari Village has not been maximized and the management of BUMDes in Balongsari Village need to be improved again so that the type of BUMDes business increases and productivity is maximized.